Extraosseous Ewing’s Sarcoma in Spinal Epidural Space (International Journal of Medical and Surgical Sciences, 2016)
Extraosseous Ewing’s sarcoma belongs to the family of neuroectodermal tumors that derive from the neural crest, characteristic of its aggressiveness. Several locations have been described, however, epidural presentation is rare. Prognosis has been improved by new oncological regimens and other therapeutic targets are being studied.
Keywords: Extraosseous Ewing’s sarcoma; Neuroectodermal tumors